Peran Kurikukum Paud Dalam Mengembangkan Potensi Anak Sejak Dini: The Role of Early Childhood Curriculum in Developing Children's Potential from an Early Age - Salsabilah, Rubi'ah; Loka, Novita (JURNAL TILA ( Tarbiyah Islamiyah Lil Athfaal ), 2024)
This article examines the role of Early Childhood Education (PAUD) curriculum in developing children's potential from an early age. The research aims to explore how an effective curriculum can optimize holistic child development through a comprehensive approach. The study employs a qualitative method with field research conducted at KB Indah Mulya, in Indralaya District, Ogan Ilir Regency, South Sumatera. Data collection techniques included observation, in-depth interviews, and documentation. Data analysis utilized Miles and Huberman's interactive model, comprising data reduction, data presentation, and conclusion drawing. Research findings reveal that effective PAUD curriculum implementation can develop children's potential through three main components: learning planning, execution, and evaluation. Early childhood education institutions with child-centered approaches and educators qualified with S1 in PAUD demonstrated significant success in optimizing physical-motor, cognitive, language, socio-emotional, artistic, and moral development. The study emphasizes the importance of a responsive, meaningful curriculum aligned with each child's individual developmental stage.